Effect of smoking regulations in local restaurants on smokers' anti-smoking attitudes and quitting behaviours. Issue 2 (30th March 2007) - Albers, Alison B; Siegel, Michael; Cheng, Debbie M; Biener, Lois; Rigotti, Nancy A
Abstract : Objective: To examine the effect of smoking regulations in local restaurants on anti-smoking attitudes and quitting behaviours among adult smokers. Design: Hierarchical linear modelling (HLM) was used to assess the relationship between baseline strength of town-level restaurant smoking regulation and follow-up (1) perceptions of the social acceptability of smoking and (2) quitting behaviours. Setting: Each of the 351 Massachusetts towns was classified as having strong (complete smoking ban) or weak (all other and no smoking restrictions) restaurant smoking regulations. Subjects: 1712 adult smokers of Massachusetts aged ⩾18 years at baseline who were interviewed via random-digit-dial telephone survey in 2001–2 and followed up 2 years later. Main outcome measures: Perceived social acceptability of smoking in restaurants and bars, and making a quit attempt and quitting smoking. Results: Among adult smokers who had made a quit attempt at baseline, living in a town with a strong regulation was associated with a threefold increase in the odds of making a quit attempt at follow-up (OR = 3.12; 95% CI 1.51 to 6.44). Regulation was found to have no effect on cessation at follow-up. A notable, although marginal, effect of regulation was observed for perceiving smoking in bars as socially unacceptable only among smokers who reported at baseline that smoking in bars was socially unacceptable. Conclusions: Although local restaurant smoking regulations did not increase smoking cessation rates, they did increase the likelihood of making a quit attempt among smokers who had previously tried to quit, and seem to reinforce anti-social smoking norms among smokers who already viewed smoking in bars as socially unacceptable.